ABOUT USING OF SECONDARY ION MASS SPECTROMETRY METHOD FOR RESEARCH OF BIOORGANIC OBJECTS - Litvinov, V. A.; Koppe, V. T.; Bobkov, V. V. (East European Journal of Physics, 2016)
The problems of application of secondary ion mass spectrometry (SIMS) with a liquid matrix for the study of objects of organic origin, as well as some aspects of the methodology of the liquid matrix using, in particular, for minimizing the effect of ion probe on the investigated object were considered. It was shown that the use of SIMS with the liquid matrix allowed to analyze reactions in a rather complicated bioorganic systems, including intermediate products of reactions, from the behavior of secondary ions characteristic for system components. Furthermore, after the necessary calibration procedure, the method permitted to determine the concentration of components during the reaction. The results of the study of the enzymatic oxidation of glucose were presented. It was shown that the use of SIMS with a liquid matrix allowed investigating the influence of radiation on materials of organic origin. The results of the study of radiation damage of molecules of arginine amino acids, glutamic acid and tryptophan under ultraviolet irradiation were represented.